Join the growing community of curious minds on IDNLearn.com. Our platform provides prompt, accurate answers from experts ready to assist you with any question you may have.

What is the solution to the equation [tex]$\frac{x}{3}+\frac{x}{6}=\frac{7}{2}$[/tex]?

A. [tex]$x=\frac{3}{2}$[/tex]
B. [tex][tex]$x=\frac{7}{3}$[/tex][/tex]
C. [tex]$x=3$[/tex]
D. [tex]$x=7$[/tex]


Sagot :

To solve the equation [tex]\(\frac{x}{3} + \frac{x}{6} = \frac{7}{2}\)[/tex], follow these steps:

1. Find a common denominator for the fractions on the left side:
- The fractions are [tex]\(\frac{x}{3}\)[/tex] and [tex]\(\frac{x}{6}\)[/tex]. The common denominator for these fractions is 6.

2. Rewrite the fractions with the common denominator:
- [tex]\(\frac{x}{3}\)[/tex] can be rewritten as [tex]\(\frac{2x}{6}\)[/tex].
- [tex]\(\frac{x}{6}\)[/tex] remains as it is.

3. Combine the fractions on the left side:
- Now we have: [tex]\(\frac{2x}{6} + \frac{x}{6}\)[/tex].
- Since they have the same denominator, we can add the numerators: [tex]\(\frac{2x + x}{6} = \frac{3x}{6}\)[/tex].

4. Simplify the combined fraction:
- [tex]\(\frac{3x}{6}\)[/tex] simplifies to [tex]\(\frac{x}{2}\)[/tex].

5. Substitute back into the original equation:
- So the equation simplifies to: [tex]\(\frac{x}{2} = \frac{7}{2}\)[/tex].

6. Solve for [tex]\(x\)[/tex]:
- Since the denominators are the same, you can equate the numerators: [tex]\(x = 7\)[/tex].

Therefore, the solution to the equation [tex]\(\frac{x}{3} + \frac{x}{6} = \frac{7}{2}\)[/tex] is [tex]\(x = 7\)[/tex].

This means the correct answer is:
[tex]\[ x = 7 \][/tex]